(untitled) (Bioagro, 2026)
In Peru and southern Ecuador, Gossypium barbadense L., or native cotton, is mainly cultivated, from which the Pima, Tangüis, and Áspero varieties originate. Eighty-two accessions of this cotton from the Lambayeque germplasm bank were characterized morphologically and agronomically. Thirty-seven descriptors (20 quantitative and 17 qualitative) were used over a period of 3 years. Cluster analysis grouped the accessions into six groups. Analysis of variance revealed that the number of bolls per plant (NBELPL) and the weight of raw cotton per plant (ALGRAM) were decisive in the grouping, with highly significant differences (p=0,001). Group 4 had the highest yield (0,853±0,199 kg of raw cotton and 224,0±40,7 acorns per plant), while groups 1 and 6 had the lowest values. Multiple correspondence analysis of the qualitative descriptors showed that flower characteristics explained 62,4 % of the total variability, standing out as the most influential factor. These results confirm the usefulness of morphological and phenotypic characterization to identify native accessions with potential for genetic improvement and application in the Peruvian textile industry.